Sedimentological characteristics and aspects of hydrocarbon potential of kinasar-1 well sediments, Bornu basin, northeastern Nigeria (2012)
Subsurface samples from Kinasar-1 well, in the Bornu basin, northeastern Nigeria, were studied to deduce the lithofacies distribution, provenance, palaeodepositional environment and paleotectonic conditions of the basin. In addition, the hydrocarbon potential of the associated shales has been highlighted. The lithological sequence comprised a basal unit of over 1300m coarse grained sandstone of the Bima Formation, overlain by 1200m shaly unit with a sandy base, belonging to the Gongila Formation. This is successively overlain by thick carbonaceous Fika Shale, and capped by over 700m of sandstone with claystone intercalations which constitute the Chad Formation. Altogether, 29 representative samples, made up of 15 Shale, 12 sandstone, and 2 claystone from the well were sampled for this study. The sandstones are angular to subrounded, coarse grained, poorly sorted, mostly coarsely skewed and platykurtic to lepturkurtic. Cross plots of textural parameters indicate that they are river sands and fluvial. Petrographic studies identify the sandstones as subarkose, with quartz mainly of monocrystalline with subordinate polycrystalline varieties. Heavy minerals comprised zircon, tourmaline, rutile, staurolite, and garnet from both the Chad and Bima Formations with average ZTR indices of 78.9 and 81% respectively. Clay mineral composition shows the predominance of kaolinte (av. 85.68%) with quartz constituting 15.32% of detrital fraction. This may be attributable to weathering of feldspar -rich rocks under humid conditions from the adjoining basement rocks of northern Nigeria. Rock - eval studies revealed that the total organic carbon (TOC) ranges from 1.02 to 2.31wt% which indicate adequate organic matter for both the Fika Shale (1.19 to 2.31wt %) and the shaly facies of the Gongila Formation (1.02 to 1.41wt%). Generally, the Hydrocarbon Index (HI) and Genetic Potential (GP) are low, with average values of 50mgHc/ gTOC and 0.82kg-1 f1 respectively, thus indicating low hydrocarbon potential. Tmax values range from 360°C to 472°C and the calculated vitrinite reflectance varies from 0.58% to 1.23% which connote thermally immature to marginally mature sediments. Cross plots of HI versus TOC and Tmax versus HI imply that majority of the sediments are types III and IV kerogen which are terrestrial precursor and gas proned. It can be deduced that the subarkosic sandstones are products of continental block provenace, derived probably from the Zambuk ridge and/or the north central basement complex of Nigeria and deposited in a fluvial environment The immature to slightly mature shales are terrestrial precursors having potential to generate gas at appropriate maturation.